2013
DOI: 10.1108/10444061311316799
|View full text |Cite
|
Sign up to set email alerts
|

True and hollow forgiveness, forgiveness motives, and conflict resolution

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 21 publications
2
28
0
2
Order By: Relevance
“…First, forgiveness may reflect an intent to heal the relationship even at the expense of maximizing one's individual outcome (i.e., sacrificing vengeful desires for the sake of repairing the relationship)-a truly cooperative or prosocial orientation in SVO terms (Van Lange, 1999), also labeled "relationship-oriented," "other-focused," or "inclusive" in the forgiveness literature (see Finkel et al, 2002;McCullough, 2008;Strelan, 2018;Strelan et al, 2013). 2 Second, forgiveness may reflect an individualistic orientation, such as trying to evade being sanctioned for violating a forgiveness norm, trying to manage one's mood, to protect one's ideal self, to regain social status or a sense of personal control, and so on (Baskin & Enright, 2004;Exline et al, 2003;Strelan & Covic, 2006;Strelan et al, 2013;Takada & Ohbuchi, 2013;Worthington & Scherer, 2004). Notably, such individualistic or "selforiented" forgiveness aims at maximizing the victim's outcomes without taking any consequences for the transgressor into account.…”
Section: Perceiving Forgivenessmentioning
confidence: 99%
“…First, forgiveness may reflect an intent to heal the relationship even at the expense of maximizing one's individual outcome (i.e., sacrificing vengeful desires for the sake of repairing the relationship)-a truly cooperative or prosocial orientation in SVO terms (Van Lange, 1999), also labeled "relationship-oriented," "other-focused," or "inclusive" in the forgiveness literature (see Finkel et al, 2002;McCullough, 2008;Strelan, 2018;Strelan et al, 2013). 2 Second, forgiveness may reflect an individualistic orientation, such as trying to evade being sanctioned for violating a forgiveness norm, trying to manage one's mood, to protect one's ideal self, to regain social status or a sense of personal control, and so on (Baskin & Enright, 2004;Exline et al, 2003;Strelan & Covic, 2006;Strelan et al, 2013;Takada & Ohbuchi, 2013;Worthington & Scherer, 2004). Notably, such individualistic or "selforiented" forgiveness aims at maximizing the victim's outcomes without taking any consequences for the transgressor into account.…”
Section: Perceiving Forgivenessmentioning
confidence: 99%
“…The development of forgiveness research in individualistic cultural contexts has been noted by some scholars, who argue that conceptions of forgiveness and the processes linked to forgiveness may be framed differently in collectivist cultural contexts (Hook, Worthington, & Utsey, 2009;Sandage, Hill, & Vang, 2003). Some empirical studies support this view; they will be discussed further below (Fu, Watkins, & Hui, 2004;Hook et al, 2013;Kurniati, Worthington, Kristi Poerwandari, Ginanjar, & Dwiwardani, 2017;Suwartono, Yeti Prawasti, & Mullet, 2007;Takada & Ohbuchi, 2013).…”
Section: Conceptions Of Forgiveness In Cultural Contextsmentioning
confidence: 96%
“…For members of these groups, the most significant function of forgiveness may be to restore closeness and group harmony. For example, research among Japanese participants found that relationship-oriented motives (e.g., desire for social harmony, sympathy for the offender) were endorsed as reasons to forgive (Fu et al, 2004; Takada & Ohbuchi, 2007, 2013). When social harmony and personal interests are in conflict, Japanese people may forgive and resolve conflict for the sake of the relationship, even if it incurs a personal cost (such as inner peace; Hook et al, 2009; Sandage et al, 2003).…”
Section: Forgiveness In Western and East Asian Contextsmentioning
confidence: 99%
“…Prior research has conceptually stated and empirically established a positive relationship between empathy and forgiveness. Forgiveness is defined as "one's willingness to abandon rightful resentment, condemnation and even subtle revenge toward the offender" (McCullough et al, 1998;Takada and Ohbuchi, 2013), which is directly driven by his/her empathy toward the offender. Empathy can directly interfere with the natural course of victims' thoughts regarding the offender.…”
Section: The Mediating Role Of Empathymentioning
confidence: 99%